2004
DOI: 10.1111/j.0300-3256.2004.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

The freshwater turtle genus Mauremys (Testudines, Geoemydidae) — a textbook example of an east–west disjunction or a taxonomic misconcept?

Abstract: a textbook example of an east-west disjunction or a taxonomic misconcept? -Zoologica Scripta , 33 , 213-221. We compare 1036 bp of the mitochondrial cytochrome b gene (cyt b ) from all six Mauremys species with 16 other taxa, representing both currently recognized subfamilies of the Geoemydidae (Geoemydinae and Batagurinae) to contribute a comprehensive dataset towards resolving the conflicting Mauremys taxonomy and phylogeography. Mauremys , a representative of the Geoemydinae, is thought to be an example of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 39 publications
8
51
0
Order By: Relevance
“…The outgroup sequences and ingroup sequences #s 2-4, 11, 21, 23, 25 are from Spinks et al (2004) and #s 9, 15 from Barth et al (2004). Note specimen #32 (R0520) is a voucher at Hainan Normal University, and #19 has no voucher because it was used in a study that required destructive sampling of the specimen.…”
Section: Appendix Amentioning
confidence: 99%
“…The outgroup sequences and ingroup sequences #s 2-4, 11, 21, 23, 25 are from Spinks et al (2004) and #s 9, 15 from Barth et al (2004). Note specimen #32 (R0520) is a voucher at Hainan Normal University, and #19 has no voucher because it was used in a study that required destructive sampling of the specimen.…”
Section: Appendix Amentioning
confidence: 99%
“…Three distinct clades were recovered from the nuDNA -M. annamensis, M. 'mutica' from Hainan Island, China, and M. mutica from mainland eastern China. However, only two distinct clades were formed by the mtDNA, with mainland Barth et al 2004;Spinks et al 2004) analyses have confirmed that the two taxa are each other's closest living relatives. However, the exact taxonomic relationship between M. annamensis and M. mutica is unclear.…”
Section: Annamensis From Central Vietnam Forming Anothermentioning
confidence: 97%
“…Initial molecular studies using mitochondrial DNA (mtDNA) found substantial differences between M. annamensis and M. mutica (Barth et al 2004;Spinks et al 2004). However, a more comprehensive mtDNA study found M. mutica to be paraphyletic with respect to M. annamensis, with M. mutica from eastern China forming one clade and • Chelonian Research Monographs,No.…”
Section: Annamensis From Central Vietnam Forming Anothermentioning
confidence: 99%
“…In recent molecular phylogenetic studies, this genus has been frequently synonymized with Mauremys along with Chinemys (e.g., Fritz and Havaš 2007;Turtle Taxonomy Working Group 2007;Lovich et al 2011) because O. sinensis, M. japonica and Chinemys spp. form a monophyletic clade and are included in a major, more inclusive clade with the other species of the genus Mauremys sensu stricto (Honda et al 2002;Barth et al 2004;Feldman and Parham 2004;Spinks et al 2004;Sasaki et al 2006;Jiang et al 2011). However, to date, no diagnostic morphological features or synapomorphies are known for the clade embracing O. sinensis, M. japonica, and Chinemys spp.…”
Section: Introductionmentioning
confidence: 99%
“…or the more inclusive clade including also all other species of Mauremys sensu stricto. To overcome this incongruence between phylogenetic relationships and taxonomic classification, two solutions have been proposed: placing all species into Mauremys or to recognize several distinct genera (Barth et al 2004;Spinks et al 2004). The oldest available name for the clade including O. sinensis, M. japonica, and Chinemys spp.…”
Section: Introductionmentioning
confidence: 99%